Perceptions on principle of priority setting in disaster triage: A Q-method study. (November 2021) - Ghanbari, Vahid; Ardalan, Ali; Zareiyan, Armin; Nejati, Amir; Hanfling, Dan; Bagheri, Alireza; Rostamnia, Leili
Highlights: It is not clear how greatest good for the greatest people can be achieved in disaster triage. Medical need was agreed to be the most important factor for patient prioritization in disaster triage. Patient survivability and medical treatment effectiveness agreed to be another two main factors for decision-making in disaster triage. Contribution to affected community and family also are important measures for making an ethical decision in disaster triage. Arrival time to a health care center or random selection should have no effect in decision making for patient prioritization in disaster triage. Abstract: Introduction: An ethical plan is required to make decisions regarding setting the priority for assisting injured patients through triage. The aim of this study was to explore the measures used to sort patients for ethical decision-making in disaster triage. Method: The participants were 54 clinicians and non-clinicians among the Iranian experts. Q-statements were selected from a literature review and face-to-face interviews. Data were analyzed by principal components factor analysis (PCA), Varimax, and hand-rotation techniques. Results: Distinct perspectives included: Saving patients with greater medical needs, survivability of patients and the community, providing effective treatment based on available capacity, maximizing health gain, supporting the human generation and productive and independent lives. Approximately 61% of the variance in decision is explained by these factors. Conclusion: A combination of saving more people and more positive outcomes has been accepted to make an ethical decision in triage. Public engagement needs to reach a more acceptable view of patients' prioritizing factors in a scarce-resource situation.